Using a biopsychosocial approach to examine differences in post-traumatic stress symptoms between Arab and Jewish Israeli mothers following a child's traumatic medical event - Sewar Hussein; Yaara Sadeh; Rachel Dekel; Efrat Shadmi; Amichai Brezner; Jana Landa; Tamar Silberg (BMC, 2021)
Abstract Background Parents of children following traumatic medical events (TMEs) are known to be at high risk for developing severe post-traumatic stress symptoms (PTSS). Findings on the negative impact of TMEs on parents' PTSS have been described in different cultures and societies. Parents from ethnic minority groups may be at particularly increased risk for PTSS following their child's TME due to a host of sociocultural characteristics. Yet, differences in PTSS manifestation between ethnic groups following a child's TME has rarely been studied. Objectives We aimed to examine: (1) differences in PTSS between Israeli-Arab and Israeli-Jewish mothers, following a child's TME, and (2) risk and protective factors affecting mother's PTSS from a biopsychosocial approach. Methods Data were collected from medical files of children following TMEs, hospitalized in a Department of Pediatric Rehabilitation, between 2008 and 2018. The sample included 47 Israeli-Arab mothers and 47 matched Israeli-Jewish mothers. Mothers completed the psychosocial assessment tool (PAT) and the post-traumatic diagnostic scale (PDS). Results Arab mothers perceived having more social support than their Jewish counterparts yet reported higher levels of PTSS compared to the Jewish mothers. Our prediction model indicated that Arab ethnicity and pre-trauma family problems predicted higher levels of PTSS among mothers of children following TMEs. Conclusions Despite reporting higher social support, Arab mothers reported higher levels of PTSS, as compared to the Jewish mothers. Focusing on ethnic and cultural differences in the effects of a child's TME may help improve our understanding of the mental-health needs of mothers from different minority groups and aid in developing appropriate health services and targeted interventions for this population.